Dynamics of humoral immunity in gingival fluid during combined immunotherapy in pediatric patients with exacerbation of chronic granulomatous periodontitis - N. M. Agarkov; Ya. V. Glagoleva; D. O. Zamulin; S. N. Gontareva (Медицинская иммунология, 2020)
Chronic granulating periodontitis among children has a high prevalence, which determines the relevance of its research, medical and social significance. The exacerbation of the disease is accompanied by various disorders in the immune system and, above all, at the local level. However, changes in local humoral immunity in children with exacerbation of chronic granulating periodontitis (CGP) have not been studied. Impact of modern immunomodulators and, in particular, Derinat, on pathological changes of local parameters of humoral immunity was not analyzed in pediatric patients with this disorder.The aim of this work is to study local humoral immunity parameters during CGP exacerbation in children and on the background of combined therapy with Derinat, Unidox-Solutab, and Tycveolum (oil extract from pumpkin seeds).The analysis of immunological disorders in gingival fluid was performed in 93 children aged 12-14 years with exacerbation of chronic granulating periodontitis, who underwent examination and treatment in Belgorod city pediatric dental clinic, and at the Department of Pediatric Dentistry of Belgorod State National Research University in 2013-2015. The patients included in the study were divided into 2 groups: control group (n = 48), receiving conventional treatment, and the main group (n = 45), who, in addition to standard therapy, were treated with Derinat, Unidox-Solutab and Tycveolum. Contents of immunoglobulins in gingival fluid were determined by turbidimetric method using the Microlab-300 photometer. Lysozyme and lactoferrin were studied by solid-phase enzyme immunoassay.Exacerbation of chronic granulating periodontitis in childhood is associated with a representative decrease of sIgA, IgA, lysozyme and lactoferrin in gingival fluid, and increased levels of IgM and IgG. Upon treatment with innovative therapy, including derinate, as one of the components, in CGP patients, there was a significant improvement of immune parameters on the 14th day of observation. Normalization of all studied parameters of local immunity was noted in the patients of main group by the 30 th day of observation. Meanwhile, only some immunological parameters reached normal reference values in the control group of patients. Conclusion. The identified new mechanisms of Derinat effects upon humoral immunity and it’s effective use during exacerbation of chronic granulomatous periodontitis in children.